Ice thickness, volume and subglacial relief of Djankuat Glacier (Central Caucasus) - I. Lavrentiev I.; S. Kutuzov S.; D. Petrakov A.; G. Popov A.; V. Popovnin V.; И. Лаврентьев И.; С. Кутузов С.; Д. Петраков А.; Г. Попов А.; В. Поповнин В. (Ice and Snow, 2015)
In this paper we present and discuss results of radio-echo sounding and modelling of ice thickness of the Djankuat Glacier. This glacier is the reference one for the Central Caucasus and was earlier studied comprehensively, but direct ice thickness measurements survey were not made so far. In 2012–2013, more than 20 km of ice-thickness measurement profiles were obtained using monopulse ground radar VIRL-6 with its central frequency of 20 MHz. Standard error of the ice-thickness measurement was 2.5%. Detailed maps of the ice-thickness and the bedrock topography based on these direct measurements were constructed for the first time. Its average ice-thickness is 31 m with the maximum of 105 m. Djankuat Glacier ice volume is 0.077±0.002 km3 when Djantugan plateau is not taken into account. Ice thickness map was supplemented by results of the ice thickness modelling using the GlabTop model. It was shown that the model reproduces the ice thickness distribution correctly, and a special approach was developed to correct model parameters using ice thickness measurements. Further on, we plan to use corrected GlabTop model for estimation glaciations of the Caucasus as well as to carry out ground radar sounding of the Djantugan plateau. Анализируются результаты радиолокационных измерений и моделирования толщины льда опорного для Центрального Кавказа ледника Джанкуат. Несмотря на всестороннюю изученность, площадная инструментальная съёмка толщины льда на этом леднике до сих пор не проводилась. В 2012–2013 гг. на леднике Джанкуат при помощи моноимпульсного радиолокатора ВИРЛ-6 с центральной частотой 20 МГц пройдено более 20 км профилей, перекрывающих основную часть ледника. Стандартная ошибка измерений составила 2,5% измеряемой величины. Впервые были построены детальные карты толщины льда и подлёдного рельефа ледника, основанные на фактических данных. Максимальная измеренная толщина ледника составляет 105 м при средней толщине 31 м. Объём ледника Джанкуат без учёта Джантуганского плато, согласно данным инструментальных ...